Governance, Commissioning and Public Health - Marks, Linda, 1951- (Book collections on Project MUSE., 2014)
Drawing on in-depth case studies across England, this book argues that governance and population health are inextricably linked. Using original research, it shows how these links can be illustrated at a local level through commissioning practice related to health and wellbeing. Exploring the impact of governance on decision-making, 'Governance, commissioning and public health' analyses how principles, such as social justice, and governance arrangements, including standards and targets, influence local strategies and priorities for public health investment.